2011
DOI: 10.1002/joc.2429
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the distributions of aggregated monthly precipitation over the La Plata Basin

Abstract: Positive trends in annual rainfall in the La Plata Basin (LPB), south of 20°S observed in the last four decades of the twentieth century were not reversed and became more statistically significant when calculated until 2005. These trends were part of a more general change in the monthly precipitation distribution including extreme precipitation.Precipitation in dry and extremely dry months (below the 35th percentile) has been decreasing in the whole LPB region south of 22°S. On the contrary, precipitation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 30 publications
0
60
0
1
Order By: Relevance
“…A second objective of this paper is to assess if there has been a discernible trend in the hail frequency in some regions of Argentina. As background, it is worth to mention that there have been important positive trends and changes in annual rainfall during the last decades of the past century over southeastern South America (Barros et al, 2000(Barros et al, , 2008 as well as an increase in heavy precipitation frequency (Re and Barros, 2009;Penalba and Robledo, 2009;Doyle et al, 2011) which might be linked to global warming. Regarding trends, it is interesting to mention that southeastern China, at a similar latitude and with a similar type of climate as eastern Argentina, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A second objective of this paper is to assess if there has been a discernible trend in the hail frequency in some regions of Argentina. As background, it is worth to mention that there have been important positive trends and changes in annual rainfall during the last decades of the past century over southeastern South America (Barros et al, 2000(Barros et al, , 2008 as well as an increase in heavy precipitation frequency (Re and Barros, 2009;Penalba and Robledo, 2009;Doyle et al, 2011) which might be linked to global warming. Regarding trends, it is interesting to mention that southeastern China, at a similar latitude and with a similar type of climate as eastern Argentina, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Doyle et al . () showed that this positive trend is due to increases in the above‐normal and extremely high rainfall months. One of the consequences of these heavy rainfalls are overbank floods which have become more frequent particularly in the La Plata Basin (Camilloni and Barros, ; Barros et al ., ; Garavaglia et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, different modes of climate variability such as El Niño‐Southern Oscillation (ENSO) (Camilloni and Barros, ; ; Grimm et al, ; Grimm and Tedeschi, ), the southern annular mode (SAM) (Silvestri and Vera, ) or even anomalies in sea ice extent around Antarctica (Saurral et al, ) lead to distinct patterns of rainfall across the basin, affecting the availability of water over the region. During the last decades, the southern part of LPB has experienced a substantial increase in precipitation (Barros et al, ; Barros et al, ; Barros Soares et al, ; Saurral et al, ) which contributed to expand the extent of the agricultural areas, although at the same time the accompanying increase in extreme precipitation (Penalba and Robledo, ; Doyle et al, ) led to frequent flooding events (Camilloni and Barros, ; Barros et al, ; Camilloni, ).…”
Section: Introductionmentioning
confidence: 99%